Economic Meaning of the Concept of “Non-Financial Reporting” - Bezverkhiy, K. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The issue related with interpretation of the economic meaning of “non-financial reporting” becomes vital in view of harmonizing the Ukrainian legal acts with EU standards, including ones on accounting. In practice, much confusion still occurs: non-financial reporting may either be seen as separated reporting, or as one identical to integrated reporting, or as an integrated reporting component. The aim of the study is to clarify the economic meaning of the concept of “non-financial reporting. A review and systematization of definitions of the economic meaning of “non-financial reporting”, given by various authors in 2009 to 2016, is made. The sample of reviewed sources includes reference literature, books, theses and theses abstracts, scientific articles and proceedings of scientific conferences. The dynamics of publication activity of researchers and economists in interpreting the economic meaning of “non-financial reporting” over this period is analyzed. It is found that the highest publication activity in interpreting the economic meaning of the term “non-financial reporting” was in 2015. Approaches to the interpretation of the economic meaning of “non-financial reporting” are summed up. It is found that the largest share of literary sources (76.32%) define non-financing reporting as a tool to meet information needs of stakeholders regarding the company’s economic, social or ecological indicators. The author’s definition of “non-financial reporting” is proposed.